2022
DOI: 10.7554/elife.76968
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering natural variation in root system architecture and growth dynamics using a robotics-assisted phenomics platform

Abstract: The plant kingdom contains a stunning array of complex morphologies easily observed above-ground, but more challenging to visualize below-ground. Understanding the magnitude of diversity in root distribution within the soil, termed root system architecture (RSA), is fundamental to determining how this trait contributes to species adaptation in local environments. Roots are the interface between the soil environment and the shoot system and therefore play a key role in anchorage, resource uptake, and stress res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Conversely, certain traits such as dry root mass, primary root length, and width were solely associated with loci on a single chromosome (Figure 2c). Past studies have found RSA traits to be polygenic (LaRue et al 2022), and these results are consistent with the suggestion that multiple GC genes distributed across the genome collectively influence traits, such as total root length and primary root tip depth, in RSA.…”
supporting
confidence: 84%
“…Conversely, certain traits such as dry root mass, primary root length, and width were solely associated with loci on a single chromosome (Figure 2c). Past studies have found RSA traits to be polygenic (LaRue et al 2022), and these results are consistent with the suggestion that multiple GC genes distributed across the genome collectively influence traits, such as total root length and primary root tip depth, in RSA.…”
supporting
confidence: 84%
“…Notably, the strategic design of the agar plates allowed the unobstructed, open-air growth of the shoots which still is a distinguishing feature, also, in the newer systems. This is also a trait in another recent platform GLO-Roots [ 97 , 98 ] which has a similar “open-top” approach, while the MultipleXLab [ 99 ] one sticks to the conventional “closed-plate” system. Having access to the leaves opens the potential for the non-invasive monitoring of the plant’s physiological parameters such as chlorophyll fluorescence and gas exchange, i.e., net photosynthetic rate, stomatal conductance, and transpiration, which are important indicators of the plant’s response to the climate and environmental changes (e.g., [ 4 , 100 , 101 ]).…”
Section: Discussionmentioning
confidence: 99%
“…While many publications suggest advanced methods of data analysis using deep learning techniques, the experimental designs and image acquisition frequently expose the root to light, which can affect the root phenotype. The development of reliable, automated image processing software is crucial to evaluate a large number of individual roots, due to their high variability, and to associate different phenotypes with specific quantitative trait loci (QTLs) (Fernandez et al ., 2022; LaRue et al ., 2022; Lube et al ., 2022; Ohlsson et al ., 2023). The extraction and analysis of multiple root traits and growth dynamics are constantly improved (Seethepalli et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%